FACEBOOK’S FUTURES - Karppi, Tero Jukka; Schrock, Andrew Richard; Herman, Andrew; McKelvey, Fenwick (AoIR Selected Papers of Internet Research, 2015)
This panel asks what will the future of Facebook and our online connectivity become; or more precisely what are the conceptual notions that emerge from Facebook’s future imaginaries. We see Facebook’s new product developments as an attempt to govern the future. We follow here Ben Anderson (2010: 778, 793) according to whom futures are anticipated and acted on through the assembling of ‘styles, consisting of statements that disclose and relate to the form of the future; practices, consisting of acts that make specific futures present; and logics, consisting of interventions in the here and now on the basis of futures.’ We set to explore the style, practices and logics behind Facebook’s attempts to connect to people and concepts currently outside their reach. These efforts include internal research on humanist design principles; inventing mobile business models and infrastructures; building data storage spaces to different parts of the world; investing to emerging technologies such as drones; and building an initiative called internet.org which would provide internet access to all over the world. These investments for the future oscillate between materiality and phenomenality of media and can be economic, affective, social, technological and cultural. Given the dominant position of Facebook in our current media ecosystem, these ideals likely reflect the crafting of a future digital global media landscape. These are new forms of media that will potentially ‘determine our situation’ (Kittler 1999), change the way we think (Hayles 2013) or at least, as Mark Hansen (2014, 37) puts it, demand us to build relationship with them. Thus, these technologies to connect the remaining world are not merely technological innovations but also connect to wider cultural, ideological and economic contexts. These new technologies shape the world and our understanding of it. The papers of this panel approach Facebook’s Futures from empirical and theoretical perspectives. On one hand the papers look at current and future software developments from e.g. Buy-button to interent.org app. On the other the papers focus on material products such as mobile phones, tablets and even drones that provide access to the site. These empirical examples lead to questions of agency and value - key concepts of Facebook’s futures discussed in each of the papers.